Prospek Nahdlatul Ulama dan Muhammadiyah Menuju Penyatuan Kalender Islam di Indonesia - Wiwik, Wiwik Triulan; Kurniati; Marilang (UIN ALAUDDIN MAKASSAR, 2024)
This was motivated by religious problems related to differences between Islamic mass organizations in the method of determining the start of the Hijriah month between Nahdlatul Ulama (imkanrukyat) and Muhammadiyah (wujudul hilal). This research aims to analyze the prospects of Nahdlatul Ulama and Muhammadiyah in the Unification of the Islamic Calendar in Indonesia. This research method is library research using an Islamic law and astronomy approach. Based on the existing methods, efforts to unify are carried out on both a national and international scale. It is necessary to have a clear, directed mechanism and jointly unite steps to realize the Islamic calendar in Indonesia. For this reason, the proposed calendar usage is the Uhadi calendar (unified Islamic calendar) and the Tawlifi calendar (Synthesized Islamic calendar). With an agreed calendar, it is hoped that this will be the best way without winning or defeating one party and still maintaining the Islamic brotherhood in Indonesia. This research has limitations so it is hoped that future researchers will complete the shortcomings and develop this research.